(untitled) (Itinerarios Educativos, 2020)
This article analyzes the reasons why families choose to send their children to public secondary schools that are managed by privates. The study focused on the city of Paraná, capital of the province of Entre Ríos, Argentina. This issue has gained relevance for constituting a problem that has been always present throughout the history of Argentine educational system. Reality shows that, at least, an important number of Argentine provinces are characterized by an exodus of middle-class sectors to the private offer, this being in no way an exclusive feature noticed for secondary schools but also for other levels of the education system. As regards the applied methodology, the analysis was based on a set of semi-structured interviews held with parents of children attending private schools. To this end, four private schools in the city that were considered representative at a theoretical level and defined by their uniqueness and idiosyncratic character were selected by means of an intentional sampling. Results indicated that private schools offer differentiated education, which is regarded by families as an appropriate strategy to plan their children’s future. Different reasons such as family tradition, discipline, social support, secularism, and the institution size constitute the roots of this choice.